1974
DOI: 10.1111/j.1095-8649.1974.tb04525.x
|View full text |Cite
|
Sign up to set email alerts
|

Food and growth of arctic char, Salvelinus alpinus (L.), in the Cumberland Sound area of Baffin Island

Abstract: Arcticchar, Sahelinusalpinus (L.), captured during the summer, 1972, in Cumberland Sound, Baffin Island, fed mainly on planktonic amphipods (Pavathenii~fo libellula, Pseudalibr-otirs glacialis), copepods (Calarius hyperboreits), and fish (Boreogadus suida, Myoxocephakus sp.), but failed to utilize coelenterates, planktonic gastropods, and epi-and infauna. The considerable variation in the species composition of the diet of char of different lengths was due primarily to size selection. The average length of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 15 publications
3
35
0
1
Order By: Relevance
“…Amphipods in addition to sand lance were also the dominant prey items in trout sampled between late August and early October in the Matamek River estuary (Whoriskey et al 1981). These observations were also consistent with earlier studies involving the anadromous form of brown trout (Salmo trutta) and Arctic char (Salvelinus alpinus) (Moore and Moore 1974;Pemberton 1976;Knutsen et al 2001). Other than a few occurrences of sticklebacks and sand lance in the spring and fall, fish were infrequently encountered in stomachs of first-year migrants captured in the SMB.…”
Section: Discussionsupporting
confidence: 86%
“…Amphipods in addition to sand lance were also the dominant prey items in trout sampled between late August and early October in the Matamek River estuary (Whoriskey et al 1981). These observations were also consistent with earlier studies involving the anadromous form of brown trout (Salmo trutta) and Arctic char (Salvelinus alpinus) (Moore and Moore 1974;Pemberton 1976;Knutsen et al 2001). Other than a few occurrences of sticklebacks and sand lance in the spring and fall, fish were infrequently encountered in stomachs of first-year migrants captured in the SMB.…”
Section: Discussionsupporting
confidence: 86%
“…The present study exemplifies how the differences in the use of surface prey (terrestrial prey and emerged aquatic insects) among sympatric species can constitute an important adaptive feature to reduce interspecific competition in riverine fish communities during the summer. Thus, our findings suggest that Studies describing the trophic ecology of Arctic charr in running waters are scarce (but see Moore & Moore, 1974;Stenzel, 1987;Sinnatamby et al, 2012;Sánchez-Hernández et al, 2016). Moore & Moore (1974) observed that small Arctic charr (\100 mm) fed mostly on Chironomidae larvae.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, our findings suggest that Studies describing the trophic ecology of Arctic charr in running waters are scarce (but see Moore & Moore, 1974;Stenzel, 1987;Sinnatamby et al, 2012;Sánchez-Hernández et al, 2016). Moore & Moore (1974) observed that small Arctic charr (\100 mm) fed mostly on Chironomidae larvae. Likewise, Stenzel (1987) found that the diet of juvenile Arctic charr is mainly composed of chironomids and other dipteran larvae.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Its distribution is circumpolar at high northern latitudes and in the limited diversity of the arctic marine food web, this fish represents the major link between the secondary producers (zooplankton) and the top carnivores (marine mammals and seabirds) (Andriashev 1964, Bradstreet', Hobson & Welch 1992b, Mansfield et al 1975, Moore & Moore 1974, Sergeant 1973. The diet of arctic cod consists mainly of copepods and amphipods (Bradstreet et al 1986).…”
Section: Introductionmentioning
confidence: 99%